Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
please help with algebraic manipulation - brain's not working!?
i want to get from (1- v/c)/√(1-v^2/c^2 ) to √((1-v/c)/(1+v/c))
I've tried several times now but i'm not getting anything. A method with all steps shown would be much, much appreciated!!!
Cheers!
2 Answers
- DaveLv 69 years agoFavorite Answer
The first thing to realize is that 1-v^2/c^2 = (1-v/c)(1+v/c)
The second thing to realize is that (1-v/c) / √(1-v/c) = √(1-v/c).
This is true for any number. 3 / √3 = √3, 4 / √4 = √4, etc.
Keeping these two things in mind, you can solve as has already been shown above:
(1-v/c) / √(1-v^2/c^2)
=
(1-v/c) / √((1-v/c)(1+v/c))
=
(1-v/c) / √(1-v/c) √(1+v/c)
=
√(1-v/c) / √(1+v/c)
=
√((1-v/c) / (1+v/c))
Hope this helps.
- 9 years ago
(1- v/c)/â(1-v^2/c^2 ) = (1-v/c)/â[(1+v/c)(1-v/c)] = â(1-v/c) /â(1+v/c) = â[(1-v/c)/(1+v/c)]